O messianismo na genealogia de Jesus em Mateus - Rodrigues, Carlos Augusto Santos (2009)
In this dissertation on the pericope Mt1,1-17, we seek to prove the fact that according to genealogy in Matthew, Jesus is the Messiah announced in the Old Testament understood from foreign, prostitutes, adulterous and sinner women. Suggesting that he is the Messiah of the excluded. We are studying the concept of messianism. We are looking for the semantic origins of Messiah. We also are studying the development of messianism in ancient Judaism, both as a social phenomenon as doctrine. We have done the exegesis of perícope and the sociological and theological reading. Finally, we are presenting the arguments that our hypothesis: as the pedigree in Matthew, Jesus is the Messiah understood from foreign prostitutes, adulterous women and sinner women. In fact the Jesus of Matthew is the Messiah of the poor and marginalised.